Evaluation of Flexible Pavement Using the 2017 Bina Marga Method Study on Darul Hikmah Street, Terong Tawah, Labuapi District - Adiman Fariyadin; Anwar Efendy; Salwa Silviana (G-Tech: Jurnal Teknologi Terapan, 2025)
Flexible pavement utilises asphalt as a binding agent. The pavement layer transmits and distributes the weight from the road or flexible pavement uniformly onto the compacted subgrade. Damage to flexible pavement results from a confluence of multiple connected factors. The purpose of the study is to ascertain the thickness of flexible pavement layers and the various forms of flexible pavement. This research employs the 2017 Bina Marga approach, utilising predicted LHR data over the design life or LHRT, to ascertain the kind and thickness of flexible pavement layers, considering the CESA4 and CESA5 values. The 2044 LHRT value for Passenger Cars and Other Light Vehicles is 33,358.7; Class 5A is 6.2; Class 5B is 4.1; Class 6A is 17.1; Class 6B is 39.1; and Class 8 or non-motorized vehicles is 280.1. The CESA4 value derived from the LHRT value was 4021566.47, whereas the CESA5 value was 469755.421. The most preferred type and thickness of flexible pavement is asphalt with a granular foundation layer, namely AC – WC pavement type at 4 cm thickness, AC – BC at 6 cm thickness, and LFA Class A at 40 cm thickness.